Peningkatan Produksi Dan Kualitas Produk Olahan Camilan Keripik Ketela Di Kec. Trawas, Kab. Mojokerto - Kurriawan Budi Pranata (Journal of Innovation and Applied Technology, 2018)
Trawas district is a major agriculture district producing fruits and vegetables. Based on the type of agriculture products, there are business actors engaged in processing agricultural products into sweet potato chips. However, there are many obstacles to produce sweet potato chips in Belik Village and Jaten Village at Trawas District. Because the processing of sweet potato snack chips is still done in a very simple way in the process of enumerating a monotonous form of products. The impact of quality and quantity of production is not good so it has not been able to compete with other cassava snack products. This low production efficiency due to limited production technology (cutter tool sweet potato) is still monoton resulting in less productivity, quantity and product quality.